Corrective Tendon Repair with Local Anesthesia following Wrist-level Replantation. Issue 3 (17th March 2022) - Lu, Yi; Hsieh, Chi-Ying; Chang, Che-Ning; Chang, Ke-Chung; Chang, Dun-Hao
Abstract : Summary: Wide-awake local anesthesia with no tourniquet has become a popular method to ensure correct tendon condition intraoperatively. We report the case of a 17-year-old man who underwent nearly total left wrist amputation and successful replantation. The misconnection of flexor tendons between the thumb, index, and middle finger was found postoperatively. At 1.5 months postreplantation, simultaneous tenolysis and corrective tendon repair were performed under local anesthesia. The proximal tendon origins were confirmed intraoperatively with the patient awake. Six months after replantation, the patient underwent extensor pollicis longus tendon shortening and pulley reconstruction under wide-awake local anesthesia with no tourniquet for thumb extension lag. After adequate rehabilitation, the functional outcome was satisfactory. This case report demonstrates that local anesthesia is a judicious method to intraoperatively facilitate correct tendon repair, tension adjustment, and direct conversation between the surgeon and the patient.